Estimasi Dampak Implementasi Kebijakan Terhadap Potensi Konservasi Energi Di Sektor Industri - Hakimul Batih (Sekolah Tinggi Teknik PLN, 2019)
Beside transportation sector, industrial sector is one of the biggest energy consumption sector.Therefore, any energy conservation effort in this sector will contribute to the energy demand reduction as targeted in the National Energy Policy (KEN) and National Energy Plan (RUEN). This study tries to estimate the potential of energy conservation in Industrial sector by implementing four energy conservation policies, mamely: 1) implementation of energy management system, 2) boiler efficiency improvement, 3) Minimum Energy Performance Standards (MEPS) implementation for electric motor, and 4) MEPS implementation for chillers. Potential of energy conservation was calculated by using Long Range Energy Alternative Planning (LEAP) software. The results of this study indicate that the implemntation of those energy conservation policies has the potential to reduce energy demands by 35 million Barrel Oil Equivalent (BOE) or by 7.9% in 2025 and 232 million BOE or 15.3% in 2050 as compared to energy demand in the Business as Usual (BAU) scenario. In sthe hort-term, (2025), the contribution of energy saving from the implementation of : energy management system, improving boiler efficiency, implementation of MEPS for electric motors, and implementation of MEPS for chillers are 1.1%, 6.3%, 0.5%, and 0% , respectivily. While, for the long -term (2050) , the contribution of each policy are 6.5%, 6%,2.2%, and 0.5%, respectively.Beside transportation sector, industrial sector is one of the biggest energy consumption sector.Therefore, any energy conservation effort in this sector will contribute to the energy demand reduction as targeted in the National Energy Policy (KEN) and National Energy Plan (RUEN). This study tries to estimate the potential of energy conservation in Industrial sector by implementing four energy conservation policies, mamely: 1) implementation of energy management system, 2) boiler efficiency improvement, 3) Minimum Energy Performance Standards (MEPS) implementation for electric motor, and 4) MEPS implementation for chillers. Potential of energy conservation was calculated by using Long Range Energy Alternative Planning (LEAP) software. The results of this study indicate that the implemntation of those energy conservation policies has the potential to reduce energy demands by 35 million Barrel Oil Equivalent (BOE) or by 7.9% in 2025 and 232 million BOE or 15.3% in 2050 as compared to energy demand in the Business as Usual (BAU) scenario. In sthe hort-term, (2025), the contribution of energy saving from the implementation of : energy management system, improving boiler efficiency, implementation of MEPS for electric motors, and implementation of MEPS for chillers are 1.1%, 6.3%, 0.5%, and 0% , respectivily. While, for the long -term (2050) , the contribution of each policy are 6.5%, 6%,2.2%, and 0.5%, respectively.